Quasi-orthogonal polarization space time block codes with signal constellations rotation and performance analysis - LI Zheng-quan1; 2; SHEN Lian-feng1 (Tongxin xuebao)
A new kind of rate 3/4 space time block code based on quaternion quasi-orthogonal and the quasi-orthogonal polarization space time block code with signal optimal constellation rotation for eight and six transmit antennas were de- signed. The pair-wise decoding algorithm was adopted at the receiver. The simulation and comparison among polarization quasi-orthogonal, rotational polarization quasi-orthogonal, quasi-orthogonal and rotational quasi-orthogonal were given respectively. The results show that there is only a little improvement by signal constellations rotation when the dual-polarized antennas are used and there is a great improvement by signal constellations rotation when the sin- gle-polarized antennas are used for bit error rate performance at same conditions.